Understanding the Complex Components of Community-Based Energy Efficiency Programs: A Study of Two Massachusetts Programs. - Brandt, Erin. (2017)
Abstract: In recent years, a variety of stakeholders have recognized the role that energy efficiency can play in tackling energy, economic and climate change crises. This recognition has evolved into a growing interest in understanding the necessary elements for increasing energy savings and participation in energy efficiency programs. This thesis explores recent interest in residential programs that have "community" elements. It analyzes two Massachusetts community efficiency programs to understand how community energy efficiency programs are designed, developed, and implemented. Comparing the programs highlights the complex components of community efficiency programs. Further, such a comparison exposes the need for energy efficiency stakeholders to produce more in-depth, detailed descriptions and program evaluations of community efficiency programs. Lastly, this thesis argues that program partners need to be better prepared to address a variety of challenges that often impede a community program from increasing program participation and energy savings.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Robert Russell.; Committee: Penn Loh.; Keywords: Energy, Urban Planning, and Public Policy and Social Welfare.